2017
DOI: 10.1186/s13058-017-0904-8
|View full text |Cite
|
Sign up to set email alerts
|

FUT8 promotes breast cancer cell invasiveness by remodeling TGF-β receptor core fucosylation

Abstract: BackgroundCore fucosylation (addition of fucose in α-1,6-linkage to core N-acetylglucosamine of N-glycans) catalyzed by fucosyltransferase 8 (FUT8) is critical for signaling receptors involved in many physiological and pathological processes such as cell growth, adhesion, and tumor metastasis. Transforming growth factor-β (TGF-β)-induced epithelial–mesenchymal transition (EMT) regulates the invasion and metastasis of breast tumors. However, whether receptor core fucosylation affects TGF-β signaling during brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 39 publications
11
142
0
Order By: Relevance
“…For these QTL regions, moreover, we found that some candidate genes can be predicted in the 11_Block2 and 19_Block5, while no candidate gene was discovered within the 12_Block2 and 16_Block1 regions. For the 11_Block2, the FUT8 was found to be a signaling receptor involved in many physiological and pathological processes [64], implying that this QTL might be related to cell growth. In the 19_Block5, the SLC9A3, EXOC3, AHRR, CEP72, PRB1 , and TPPP genes were predicted.…”
Section: Discussionmentioning
confidence: 99%
“…For these QTL regions, moreover, we found that some candidate genes can be predicted in the 11_Block2 and 19_Block5, while no candidate gene was discovered within the 12_Block2 and 16_Block1 regions. For the 11_Block2, the FUT8 was found to be a signaling receptor involved in many physiological and pathological processes [64], implying that this QTL might be related to cell growth. In the 19_Block5, the SLC9A3, EXOC3, AHRR, CEP72, PRB1 , and TPPP genes were predicted.…”
Section: Discussionmentioning
confidence: 99%
“…EMT-related genes such as COL11A1, COL8A2, and ADAM12 that are overexpressed in mCA could thus be potential biomarkers for canine invasive mCA, similarly to human mCA (Freire et al, 2015;Kleinert et al, 2015;Ma et al, 2015). In the glycolysis pathway, PLOD1/2, FUT8 and TSTA3 are deregulated genes that participate in metabolism and glycolytic processes, which can influence the malignant transformation of cells, tumour development and metastasis (Gilkes et al, 2013;Kim et al, 2012;Tu et al, 2017). Among the targets that are strongly differentially expressed between CAS from mCA and adenoma, we validated the selective down--regulation of ARVCF in adenoma.…”
Section: Results Transcriptomic Profiling Of Matched Cas and Normal Smentioning
confidence: 88%
“…The addition of a 1,6 linked fucose to the chain initiating GlcNAc on complex N-glycans is catalyzed by the fucosyltransferase, FUT8 (Yang et al, 2017). FUT8-mediated core-fucoylation has been implicated as a driver of cancer invasiveness in breast cancer by fucosylation of TGF-β (Tu et al, 2017), in colorectal cancer through a p53-mediated mechanism (Noda et al, 2018), in melanoma by fucosylation of L1CAM (Agrawal et al, 2017), through a β-catenin– and LEF-1–dependent mechanism in nonsmall cell lung cancer (Chen et al, 2013), and through miRNA regulation of fucosylation in hepatocellular carcinoma (Cheng et al, 2016b).…”
Section: Critical Glycan Moieties Aberrantly Expressed In Cancermentioning
confidence: 99%